DEEP UPPER-MANTLE MELTING BENEATH THE TASMAN AND CORAL SEAS DETECTED WITH MULTIPLE SCS REVERBERATIONS - Courtier A.M.; Revenaugh J. (My University, 2007)
Multiple ScS reverberations are used to search for mantle reflectors beneath the Tasman and Coral Seas with a hierarchical waveform-inversion/migration method. In addition to the major transition zone discontinuities, a low-velocity layer above the 410-km discontinuity is detected. The top of the low-velocity layer lies at an average depth of 352 km, indicating that the layer could be more than 70-km thick if it persists to the 410-km discontinuity, which occurs at an average depth of 420 km along paths containing the low-velocity layer. We attribute the low velocities to partial melt resulting from volatile-induced melting. The considerable thickness of the partial melt layer may require thin films of a hydrous melt with a zero-degree dihedral angle surrounding grains or the combined effect on melting of the addition of both water and carbon to the deep upper mantle via subduction. Although the depths of the transition zone discontinuities do not indicate that the transition zone itself is rich in water, the impedance contrasts do contain a subtle signature that could be related to transition zone water, namely a decrease in the impedance contrast across the 410-km discontinuity and a relatively strong 520-km discontinuity. © 2007 Elsevier B.V. All rights reserved.
Keywords: DISCONTINUITIES; LOW-VELOCITY ZONE; MANTLE; PARTIAL MELTING; TRANSITION ZONE; WATER